Legal surveillance in health: The centrality of health law for the materialization of the constitutional right to health (Research, Society and Development, 2021)
The article, built from an exploratory methodology, investigates the possible centrality of health law for the materialization of the constitutional right to health. Initially, it delimits the health right, understood as a collective right and forming an autonomous legal field, with emphasis on health surveillance, given its character of reducing risks, diseases and illnesses. Therefore, two infra-constitutional laws were analyzed, the Organic Health Law and the Sanitary Surveillance Law, in order to conceptualize this term; and the Federal Constitution of 1988, in order to identify the administrative and legislative powers in public health and specifically in sanitary surveillance. The result found is that the State will only be able to fulfill its constitutional duty when it is equipped with a robust legal instrumentation sanitary, capable of materializing the right to health in this public perspective.